Renal Tubular Acidosis an Adverse Effect of PD-1 Inhibitor Immunotherapy. (31st January 2018) - El Bitar, Sandy; Weerasinghe, Chanudi; El-Charabaty, Elie; Odaimi, Marcel
Abstract : Immune checkpoint blockade therapy is gaining popularity among oncologists for treatment of solid and hematologic malignancies. The widespread use of these agents resulted in increasing incidence of renal immune-related adverse events. Reported renal toxicity described so far includes acute interstitial nephritis, minimal change disease, and immune complex glomerulonephritis. We report the case of a 79-year-old female with metastatic non-small cell lung cancer on anti-PD-1 therapy nivolumab. After the 4th administration of nivolumab, the treatment course was complicated with normal anion gap metabolic acidosis. Urine and blood studies were in favor of distal renal tubular acidosis (RTA). Following a negative workup for an underlying etiology, immunotherapy-induced RTA was suspected. Withholding of the offending agent and initiation of steroid therapy resulted in adequate response. The present report provides the first presentation of RTA as a renal immune-related adverse event secondary to nivolumab. Nephrologists and oncologists should be familiar with potentially life-threatening renal side effects induced by immune checkpoint inhibitors.